Design of a Student Payment System Based on Virtual Account - Moh Anshori Widya; Nurul Aini (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Payment media is one of the important things that must be considered in the world of education in order to make it easier for students to make payments. In the category of Vocational High School (SMK) education level, not many schools use virtual account-based payment technology. In some schools, payment administration services are still carried out conventionally with various weaknesses including causing many queues that cause health protocol violations, unstructured administration so that errors in reporting often occur and open opportunities for fraud in payments. Based on the various weaknesses above, a payment system is needed that can overcome these problems. The payment model used is a virtual account which is commonly used in the current era. In this study the method used is research and development (R & D). This research resulted in a virtual account-based payment system belonging to Bank Rakyat Indonesia (BRI). The method used in the virtual account is polling with a certain time interval. This payment system is expected to improve service quality and ease of payment.